Development and production of cherry tomato irrigated with different concentrations and availabilities of wastewater - DE SOUSA, Francielly Guieiro Gomes [UNESP]; Carvalho, RENATA DA SILVA CUBA DE [UNESP]; DE MELO, Mara Rúbia Mendes [UNESP]; Sartori, Maria Márcia Pereira [UNESP]; Hélio Grassi Filho, E. [UNESP] (Brazilian Journal of Irrigation and Drainage - IRRIGA, 2019)
Due to the scarcity of fresh water on the planet, studies seeking alternative and better methods for the economical use of water are important. Therefore, this study aimed to evaluate the effects of different concentrations and availabilities of wastewater on the development and fruit production of cherry tomato plants grown in a greenhouse. The experiment was conducted from August to December of 2015, and used a drip irrigation system with class-A pan evaporation scheduling method. Water from domestic sewage was used at four different dilutions (25, 50, 75, and 100% reused wastewater) and under two different crop evapotranspiration depths (70 and 100%). Height (H), stem diameter (SD), green phytomass (GPM), dry phytomass (DPM), fruit weight (FW), and leaf water potential (Ψl) were evaluated in plants grown under each combination of conditions. The results showed that both the different levels and dilutions of reused wastewater had significant individual effects on the agronomic parameters evaluated during the crop development, but there were no significant effects of the interaction between these two factors. Further, better crop yields were obtained from plants irrigated under 100% evapotranspiration conditions regardless of the dilution of wastewater used.
Desenvolvimento e produção do tomate cereja irrigado com diferentes concentrações e disponibilidade de água residuária
Keywords: Evapotranspiration; Irrigation scheduling; Lycopersicon esculentum L; Reuse